Knowledge, attitudes, and practices among Chinese reproductive-age women toward uterine adenomyosis - Ren, Ruofei; Li, Hongye; Zhang, Jie; Li, Xuhua; Yuan, Liqing; Li, Dongxiao; Shan, Shuzhi; Shi, Bin; Jiang, Jing (Frontiers in Medicine, 2024)
Objective This study aimed to assess the knowledge, attitudes and practices (KAP) among Chinese reproductive-age women toward uterine adenomyosis. Methods This web-based cross-sectional study was conducted between April 2023 and September 2023 at the Second Hospital of Hebei Medical University. A self-designed questionnaire was developed to collect demographic information of reproductive-age women, and assess their KAP toward uterine adenomyosis. Results A total of 520 valid questionnaires were collected. Among the participants, 127 (24.42%) were diagnosed with uterine adenomyosis, and 120 (23.08%) were accompanied by uterine fibroids. The mean knowledge, attitudes and practices scores were 3.54 ± 3.72 (possible range:0–10), 20.96 ± 3.19 (possible range:5–25) and 24.01 ± 4.95 (possible range:7–35), respectively. The structural equation model demonstrated that knowledge had direct effects on attitudes and practices, as indicated by a path coefficient of 0.714 (p < 0.001) and 1.510 (p < 0.001), respectively. Moreover, attitudes had direct effects on practices, with a path coefficient of 0.226 (p = 0.001). Conclusion The findings revealed that reproductive-age women have insufficient knowledge, negative attitudes, and poor practices toward the uterine adenomyosis. Comprehensive training programs are needed to improve reproductive-age women practices in this area.